Race, Faith, and Legal Personhood: A Maqasid Al-Shari‘ah-Based Critique of Discrimination in Muslim Societies - Arip Purkon (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article examines systemic racial and religious discrimination in Muslim societies through the lens of maqasid al-shari‘ah with a particular focus on the concept of legal personhood. Despite Islam’s normative emphasis on equality and justice, marginalized groups such as converts, non-Muslims, and ethnic minorities continue to face exclusion in both social and legal frameworks. Using a qualitative-critical approach, this study demonstrates how such practices contradict the higher objectives of Islamic law, particularly the preservation of life (hifz al-nafs), religion (hifz al-din), and human dignity (hifz al-karamah). The article argues that reformulating legal personhood through a maqasid-oriented perspective is necessary to dismantle discriminatory structures and to ensure substantive justice. By positioning maqasid al-shari‘ah as both a moral and legal framework, this study highlights its emancipatory potential for promoting inclusivity, equality, and human rights in multicultural and multireligious contexts.